Training for Improved Decentralized Service Delivery – A case study from Uganda - Niwagaba, B.C.; Nalubega, M.; Kulabako, R. (WEDC, Loughborough University, 2004)
The introduction of decentralization and decentralized service delivery in Uganda placed an increased demand for qualified personnel at the districts and lower levels. Despite this, there were no efforts in the past to enlighten students and trainers at Makerere University about the existing gaps and opportunities available in districts so that the training could be tuned to the needs of the districts. In the year 2000, the Department of Civil Engineering in Makerere University started a pilot project to attach students to the technical departments of the district local governments to undertake internship training for a period of 8 weeks. The students were supervised by staff from districts and the Department of Civil Engineering, Makerere University. The project was financed by the Rockefeller foundation and the World Bank. Since then, 72 students (11 during the pilot and 61 during the full implementation phase) have undergone internship training in 9 districts in Uganda. Eleven (11) Makerere staff and over 90 district staff were involved in the project. A training manual was developed, relevant research to solve technical problems and assist the districts in improved service delivery was identified, and efforts are under way to evaluate the project and quantify the impact.